Lokalitas Tafsir Rahmat Karya H. Oemar Bakry - Ahmad Daiyan (Program Studi Ilmu Al-Qur'an dan Tafsir, 2021)
Interpretation studies in Indonesia have their own local wisdom. In an effort to understand the Qur'an and convey the messages contained in it to the public, of course the use of locality elements can make it easier for the community to understand the contents and explanations of the verses of the Koran. The purpose of this research is to reveal locality aspects in H. Oemar Bakry's Tafsir Rahmat. This article discusses the locality of Rahmat's interpretation, which is one example of interpretation in Indonesia. In fact, there are many other works of interpretation that have developed in Indonesia, including Turjuman al-Mustafid, which was written by a well-known scholar named Shaykh Abd al-Rauf as-Sinkili, who came from Aceh. Tafsir Faidl al-Rahman written by Syekh Soleh Darat, Semarang, and Tafsir Marah Labid or better known as Tafsir Munir by Syekh Nawawi al-Bantani from Banten. In the following era, insight into the interpretation of the Koran in Indonesia was enriched by the presence of al-Ibriz by KH Bisri Musthofa, father of the charismatic figure KH Musthofa Bisri from Rembang, Central Java, as well as Tafsir Al-Azhar by Haji Abdul Malik Karim Amrullah or known as Buya Hamka. He is an influential figure as well as the first Chairman of the Indonesian Ulema Council (MUI) from Agam Regency, West Sumatra, and there are many other examples of interpretations that have developed in Indonesia. This research category is qualitative research with library research. The method that the writer uses in collecting data and the data analysis method that the writer uses is descriptive-analytical.